The Evolution of Early Islamic Ethics (American Journal of Islam and Society, 2001)
This article reviews Hellenic’ and Islamic ethics before the middle ofthe eleventh century. It begins with the ethics of the pre-Islamic Arabsand then describes the ethics of the Qur’an, hadith (PropheticTradition), adab2, Sufism, theology and philosophy. We attempt to providehere, as far as possible, a comprehensive, but not necessarilyexhaustive, overview of the unfoiding of Islamic ethics from the periodof Prophet Muhammad to Miskawayh (422/1030), the first Muslimmoral philosopher who made a conscious effort to Islamize andintegrate Hellenic elements within his ethical treatise and to make itpart of the Islamic intellectual legacy. Such an overview is intendedto provide an approximate picture of the evolution of Islamic ethicaltrends, which have modified the old Arabian ideal of muru’ah(manliness) into a new ideal of virtuous happiness in this world and inthe Hereafter. Hellenic ethics have inspired Muslim philosophers fromthe time of Miskawayh to develop a more systematic exposition ofIslamic ethics, and we hope that this review of the early ethics of Islamwill provide a better appreciation of the early sources that have hapedthe ethics of later Islamic moralists such as al-Raghib al-Isfahani(d. 433/1050) and al-Ghazzaii (505/1111), who have had a lastingimpact on Muslim thinkers up to today.